2020
DOI: 10.1002/tqem.21718
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel production from waste chicken oil using nanoeggshell heterogeneous catalyst with isopropyl ether as cosolvent

Abstract: The main aim of the present work is to produce biodiesel from waste chicken fat using a nanoeggshell heterogeneous catalyst. For the first time, isopropyl ether was used as cosolvent and investigated the effects of transesterification factors affecting the biodiesel yield. The eggshell has been activated in the muffle furnace at 900°C and was further characterized by using X‐ray diffraction analysis, Fourier transform infrared spectrometer, thermogravimetric analysis, transmission electron microscopy, Brunauer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The viscosity, which is a gauge of oil's resistance to shearing, was 6.58 cP. This value is within the previously stated range (15.15 -15.9 cP) for waste used oil(Cholapandian et al, 2022: Kirubakaran andArul, 2020).…”
supporting
confidence: 84%
“…The viscosity, which is a gauge of oil's resistance to shearing, was 6.58 cP. This value is within the previously stated range (15.15 -15.9 cP) for waste used oil(Cholapandian et al, 2022: Kirubakaran andArul, 2020).…”
supporting
confidence: 84%
“…This is followed by an article (Bichueti et al, 2021) on how the sustainable water management can contribute to business performance of the mining industry in Brazil. Two more articles (Kirubakaran and Arul Mozhi Selvan, 2021;Rajeswari et al, 2021) then discuss the pretreatments and usage of novel catalysts in biofuel production. This is followed by an article (Aravind et al, 2021) that provides a technique to reduce the consumption of fossil fuel by the addition of nanoparticles to the fuel blend.…”
mentioning
confidence: 99%
“…The study showed that hot water pre-treatment produced good outcomes and the additive prevented redeposition of the lignin on the pre-treated biomass surface. Further, Kirubakaran and Arul Mozhi Selvan (2021), have evaluated the production of biodiesel from waste chicken oil using nano-eggshell heterogeneous catalyst with isopropyl ether as cosolvent. The authors have provided a flow chart of biodiesel production processes-the waste chicken fat was microwaved to extract oil and based on the free fatty acid content it was pre-treated before transesterification.…”
mentioning
confidence: 99%